Novel Antimicrobial Peptide from Temporin L in The Treatment of Staphylococcus pseudintermedius and Malassezia pachydermatis in Polymicrobial Inter-Kingdom Infection - Rosa Bellavita; Adriana Vollaro; Maria Rosaria Catania; Francesco Merlino; Luisa De Martino; Francesca Paola Nocera; Marina DellaGreca; Francesca Lembo; Paolo Grieco; Elisabetta Buommino (MDPI AG, 2020)
Interkingdom polymicrobial diseases are caused by different microorganisms that colonize the same niche, as in the case of yeast-bacteria coinfections. The latter are difficult to treat due the absence of any common therapeutic target for their elimination, both in animals and humans. Staphylococcus pseudintermedius and Malassezia pachydermatis belong to distinct kingdoms. They can colonize the same skin district or apparatus being the causative agents of fastidious pet animals' pathologies. Here we analysed the antimicrobial properties of a panel of 11 peptides, derived from temporin L, against Malassezia pachydermatis. Only peptide 8 showed the best mycocidal activity at 6.25 μM. Prolonged application of peptide 8 did not cause M. pachydermatis drug-resistance. Peptide 8 was also able to inhibit the growth of Staphylococcus pseudintermedius, regardless of methicillin resistance, at 1.56 μM for methicillin-susceptible S. pseudintermedius (MSSP) and 6.25 μM for methicillin-resistant S. pseudintermedius (MRSP). Of interest, peptide 8 increased the susceptibility of MRSP to oxacillin. Oxacillin MIC value reduction was of about eight times when used in combination with peptide 8. Finally, the compound affected the vitality of bacteria embedded in S. pseudintermedius biofilm. In conclusion, peptide 8 might represent a valid therapeutic alternative in the treatment of interkingdom polymicrobial infections, also in the presence of methicillin-resistant bacteria.